Konsep Al-urf dalam Perkembangan Society 5.0 Perspektif Fikih Kontemporer - Afida Wahyuni; Harisah (LP2M IAI Miftahul Ulum Pamekasan, 2023)
The challenge in the progress of the times that has been in society 5.0, it is required that all layers of law also develop to keep up with these developments, including sharia law that must still be able to be applied. Thus it is not uncommon for the law to apply based on 'Urf. 'Urf which is used as a source of law for an action must exist at the time the action was carried out. There is no affirmation (nas) that contradicts 'urf. The use of 'urf will not result in the exclusion of certain texts from the Shari'at, because the texts of Syara' must take precedence over 'urf. If the Syara text' can be combined with 'urf, then the 'urf can still be used The results of the study show that: First, in society 5.0 to keep pace with the progress of the times, the concept of urgency is urgent to be used as a source of law. However, 'Urf can be said as a word and deed that involves a habit that is often done. In the era of society 5.0, every activity is easily carried out so that the urf urf must be analyzed to always be in accordance with the demands of the times and remain based on sharia. 'Urf is considered as one of the sources of law, where many elements are taken from applicable laws, then issued in the form of articles in the law. The conditions for 'urf as a source of Islamic law are, 'urf must apply continuously or mostly apply, 'urf which is used as a source of law for an action must exist at the time the action was carried out, there is no affirmation (nas) that contradicts 'urf, usage' urf will not result in the exclusion of definite passages from the Shari'at. Second, 'Urf in the view of Urf jurisprudence does not conflict with the texts so that the law contained in the texts cannot be applied. 'Urf like this cannot be used as a sharia argument', because the insult of 'urf can only be accepted if there is no text containing the law of the problem at hand. Third, urf is used as a source of law with maslahah considerations.